Nf2 orchestrates β-arrestin2-biased PTH1R signaling to couple bone mass with skeletal integrity - Junguang Liao; Yiliang He; Chenyang Zhang; Qitao Qian; Yuping Huang; Qi Zhang; Panpan Shen; Chenhe Zhou; Mengrui Wu; Guiqian Chen (Proceedings of the National Academy of Sciences, 2026)
Precise spatiotemporal regulation of parathyroid hormone (PTH) and PTH-related peptide signaling through the parathyroid hormone receptor 1 (PTH1R) is fundamental to skeletal development and metabolic bone remodeling, yet the intracellular mechanisms that fine-tune this signaling remain a central unanswered question. Here, we identify neurofibromin 2 (Nf2) as an essential regulator of PTH1R trafficking and signaling. Conditional knockout of Nf2 in chondrocytes results in short-limbed dwarfism, disrupted growth plate organization, and suppressed chondrocyte proliferation and hypertrophy, and a paradoxical bone phenotype marked by trabecular hyperproliferation and cortical thinning. Mechanistically, Nf2 binds to the PTH1R C-terminal domain (464–591 aa) to promote selective receptor internalization via β-arrestin2 without altering G protein–coupled receptor kinase-mediated PTH1R phosphorylation. Loss of Nf2 decouples PTH1R from β-arrestin2‐mediated endocytosis, leading to sustained and amplified signaling through the cAMP‐CREB‐pSOX9 (S181) and VEGF axis. Consequently, Nf2 -deficient mice exhibited bone changes similar to those induced by the PTH1R agonist abaloparatide. These findings establish Nf2 as a chondrocyte‐intrinsic gatekeeper of PTH1R signaling and uncover a cellular mechanism for bone homeostasis by targeting Nf2‐mediated β-arrestin2 recruitment.